A Comparison of General Anesthesia and Regional Anesthesia as a Risk Factor for Deep Vein Thrombosis Following Hip Surgery: A Critical Review - Prins, Martin H; Hirsh, Jack (Thrombosis and Haemostasis, 1990)
We evaluated the evidence in support of the suggestion that the risk of deep vein thrombosis after hip surgery is lower with regional than with general anesthesia. A literature search was performed to retrieve all articles which reported on the incidence of postoperative thrombosis in both fractured and elective hip surgery. Articles were included if the method of anesthesia used was reported and if they used mandatory venography. Based upon the quality of study design the level of evidence provided by a study was graded.In patients who did not receive prophylaxis there were high level studies in elective and fractured hip surgery. All studies showed a statistically significantly lower incidence of postoperative deep vein thrombosis with regional anesthesia (relative risk reductions of 46-55%). There were no direct comparative studies in patients who received prophylaxis. However, between study comparisons did not show even a trend towards to lower incidence of postoperative thrombosis with regional anesthesia.